Associations between neurochemical receptor genes, 2D:4D, impulsivity and relationship quality. (21st December 2018) - Pearce, Eiluned; Wlodarski, Rafael; Machin, Anna; Dunbar, Robin I. M.
Abstract : The ratio between the second and fourth digits (2D:4D) has been widely used as a proxy for fetal exposure to androgens and has been linked to a number of sociosexual traits in humans. However, the role of genes in this equation remains unknown. Here ( N = 474), we test, firstly, for associations between 2D:4D and single-nucleotide polymorphisms (SNPs) in nine neurochemical receptor genes ( AR, OXTR, AVPR1A, OPRM1, DRD1/2, ANKK1, 5HTR1A/2A ), and secondly, whether digit ratios mediate the relationship between genetic variation and sociosexuality. We demonstrate significant associations between AR, OPRM1 and AVPR1A and 2D:4D. Moreover, mediation analysis indicates that, in women, AR and OPRM1 variation drives digit ratios, which are related positively to impulsivity and, for OPRM1, negatively to romantic relationship quality. Although these findings are subject to multiple testing issues, this study provides preliminary evidence that in women genetic factors may affect both impulsivity and perceived relationship quality through influencing factors indexed by digit ratios.